Histocompatibility antigen, class i, g (Hla-g)’s role during pregnancy and parturition: A systematic review of the literature - Tantengco, Ourlad Alzeus G.; Richardson, Lauren; Lee, Alan; Kammala, Ananthkumar; Silva, Mariana de Castro [UNESP]; Shahin, Hend; Sheller-Miller, Samantha; Menon, Ramkumar (MDPI, 2021)
Introduction: Immune homeostasis of the intrauterine cavity is vital for pregnancy mainte-nance. At term or preterm, fetal and maternal tissue inflammation contributes to the onset of labor. Though multiple immune-modulating molecules are known, human leukocyte antigen (HLA)-G is unique to gestational tissues and contributes to maternal–fetal immune tolerance. Several reports on HLA-G’s role exist; however, ambiguity exists regarding its functional contributions during pregnancy and parturition. To fill these knowledge gaps, a systematic review (SR) of the literature was conducted to better understand the expression, localization, function, and regulation of HLA-G during pregnancy and parturition. Methods: A SR of the literature on HLA-G expression and function reported in reproductive tissues during pregnancy, published between 1976–2020 in Eng-lish, using three electronic databases (SCOPE, Medline, and ClinicalTrials.gov) was conducted. The selection of studies, data extraction, and quality assessment were performed in duplicate by two independent reviewers. Manuscripts were separated into three categories: 1) expression and localization of HLA-G, 2) regulators of HLA-G, and 3) the mechanistic roles of HAL-G. Data were ex-tracted, analyzed, and summarized. Results: The literature search yielded 2554 citations, 117 of which were selected for full-text evaluation, and 115 were included for the final review based on our inclusion/exclusion criteria. HLA-G expression and function were mostly studied in placental tissue and/or cells and peripheral blood immune cells, while only 13% of the studies reported data on amniotic fluid/cord blood and fetal membranes. Measurements of soluble and membranous HLA-G were determined mostly by RNA-based methods and protein by immunostaining, Western blot, or flow cytometric analyses. HLA-G was reported to regulate inflammation and inhibit im-mune-cell-mediated cytotoxicity and trophoblast invasion. Clinically, downregulation of HLA-G is reported to be associated with poor placentation in preeclampsia and immune cell infiltration during ascending infection. Conclusions: This SR identified several reports supporting the hypothe-sized role of immune regulation in gestational tissues during pregnancy. A lack of rigor and repro-ducibility in the experimental approaches and models in several reports make it difficult to fully elucidate the mechanisms of action of HLA-G in immune tolerance during pregnancy.
Keywords: Antigen; Fetal membranes; Immune tolerance; Placenta; Pregnancy